Digitalization in dental education - Escobar-Taipe, Allison Michel; Rivera-Marcatinco, Milvia; Veliz-Vicharra, Selene; Mattos-Vela, Manuel Antonio (Revista Facultad de Odontología Universidad de Antioquia, 2023)
The implementation of technological tools in dental education over the years has allowed the student to improve their performance in the preclinical field of their training, developing fine motor skills, currently this issue has become relevant due to the health situation of COVID-19. The objective was to describe digitalization in dental training, the technological tools used and the students´ perception of digital education in dentistry. An electronic review of the PubMed, SciELO, LILACS and ScienceDirect databases was carry out in search of articles published in English and Spanish in the period 2015 to 2022. One hundred fifty-six articles were reviewed, selecting 50 directly related to the subject of study. It is concluded that there are various digital tools that can be used in the training of professionals in dentistry; furthermore, exclusive online learning generates better results than traditional learning; and exclusive online learning, which was used during the COVID-19 pandemic lockdown, demonstrated a high degree of student dissatisfaction.